Effect of crossing film among glass fibers on blanket performance. Issue 4 (9th December 2019) - Wu, Cao; Chen, Zhaofeng; Wang, Fei; Ye, Xinli; Li, Shun; Zhang, Duanyin; Yang, Lixia
Abstract: An effective film construction was provided as a noise‐reducing materials based on self‐assembled polymer film supported by ultralight glass fiber blanket (UGFB) skeleton. The synthesized polymer film enhanced UGFB structure shows about 60% improvement over a broad frequencies compared to neat UGFB. The sound transmission loss has a remarkably increasing of 16.59 dB at 4 kHz. The reinforced acoustic performances was created by the structural optimization of UGFB/UMPR‐film, owing to the observably enhanced tortuosity in sound waves transmission and reinforced surface area, which can induce more viscous and thermal losses when the acoustic wave consumes in the semiopen pore construction. Moreover, the UGFB/UMPR‐film demonstrates 7.4 times increasing in breaking strength (width direction) and the degrees of uniformity lower than 0.0771. The manufacture of this new acoustic damping materials is low cost, structural controllable, and easy to large‐scale preparation, making it can be applied in multitudinous applications.